2003
DOI: 10.1002/jmri.10340
|View full text |Cite
|
Sign up to set email alerts
|

Biliary motor function in gallstone patients evaluated by fatty‐meal MR cholangiography

Abstract: Purpose:To investigate the possibility of evaluating biliary motor function with magnetic resonance cholangiography (MRC). Materials and Methods:Twenty patients with gallstones and 30 control subjects were studied using fatty-meal MRC. After baseline MRC, they were encouraged to drink 250 mL of milk and underwent postprandial MRC every 10 minutes for 60 minutes. Postprandial changes in gallbladder volume and the diameter of the common duct were assessed as indicators of gallbladder contractility and biliary ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…The gallbladder ejection fraction following the infusion of cholecystokinin has been found to correlate with that measured at hepatobiliary scintigraphy performed with HIDA. It is possible to assess the patency and range of contractions of that portion of the bile duct covered by the sphincter of Oddi with pharmacodynamic MR cholangiopancreatography after the ingestion of a fatty meal or the infusion of secretin (52).…”
Section: Functional Evaluation Of the Gallbladder In Patients With Acmentioning
confidence: 99%
“…The gallbladder ejection fraction following the infusion of cholecystokinin has been found to correlate with that measured at hepatobiliary scintigraphy performed with HIDA. It is possible to assess the patency and range of contractions of that portion of the bile duct covered by the sphincter of Oddi with pharmacodynamic MR cholangiopancreatography after the ingestion of a fatty meal or the infusion of secretin (52).…”
Section: Functional Evaluation Of the Gallbladder In Patients With Acmentioning
confidence: 99%
“…Other stimulants for gallbladder contractility have been studied as well, especially during shortages of pharmacologic CCK, such as a lactose-free fatty meal [42,43,44,45,46], including the use of a fatty meal during magnetic resonance imaging (MRI) cholangiography to assess GBEF [47]. Indeed, Marciani et al [48] evaluated a number of food products on gallbladder contractility by studying the changes in gallbladder size with use of MRI, and found that long-chain fatty acids was the most potent stimulator of gallbladder contractility and also induced the highest serum concentration of CCK.…”
Section: Diagnostic Modalitiesmentioning
confidence: 99%
“…Meal composition varied widely, including dried egg yolk, 13 milk, [14][15][16][17] half milk and half cream, 18,19 Lipomul (corn oil emulsion marketed by Upjohn and discontinued in 1979), 20 corned beef and cheese sandwich, 12 bacon roll, 21 a candy bar, 22 and dietary supplements. 23 In 1 study, sham feeding was used, involving chewing of food, without ingestion.…”
Section: Resultsmentioning
confidence: 99%